2018
DOI: 10.1371/journal.pone.0195218
|View full text |Cite
|
Sign up to set email alerts
|

Unsafe disposal of feces of children <3 years among households with latrine access in rural Bangladesh: Association with household characteristics, fly presence and child diarrhea

Abstract: BackgroundYoung children frequently defecate in the living environment in low-income countries. Unsafe child feces disposal has been associated with risk of diarrhea. Additionally, reported practices can underestimate socially undesirable unhygienic behaviors. This analysis aimed to assess (1) the sensitivity of reported child feces disposal practices as an indicator for observed presence of human feces in the domestic environment, (2) household characteristics associated with reported unsafe feces disposal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
58
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 25 publications
24
58
5
1
Order By: Relevance
“…This gure is higher than the national average where proportion of safe disposal of child faeces was 72% (15). Our ndings disagree with the results from rural Bangladesh which reported 80% unsafe disposal of children faeces (34). Safe disposal of children faeces in our study is due to availability of pit and ush latrine which allow caretakers to throw or rinse faeces easily.…”
Section: Discussioncontrasting
confidence: 99%
“…This gure is higher than the national average where proportion of safe disposal of child faeces was 72% (15). Our ndings disagree with the results from rural Bangladesh which reported 80% unsafe disposal of children faeces (34). Safe disposal of children faeces in our study is due to availability of pit and ush latrine which allow caretakers to throw or rinse faeces easily.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, other work in our study area indicated that, among households where child feces are not disposed of in a latrine, 64% reported disposing of them in the bushes surrounding the compound, 18% in open waste heaps and 13% in drains while only 11% left the feces on the ground. 44 However, human feces likely contribute to domestic fecal contamination through other routes, such as latrines draining into ponds/canals or pits leaking into the environment. Indeed, ponds with a latrine within 10 m and ponds receiving latrine effluent had higher E. coli levels in our study, consistent with previous evidence from rural Bangladesh.…”
Section: Resultsmentioning
confidence: 99%
“…Our modifications were: inclusion of infant and new born faecal management (thus making it more explicit as part of the principle of all inclusive household faecal containment); restricting ourselves to hand washing with soap only but not soap substitutes; and finally defining an overall hygiene behaviour indicator by combining all the three key hygiene behaviour indicators. Infant and new born faecal management (now explicit in our framework) is key in the reduction of incidence of diarrheal disease amongst infants ( Godana and Mengiste, 2013 ; Islam et al., 2018 ). Although soap substitutes could be as good as soap itself ( Potter et al., 2011 ), however, they stand the risk of becoming contaminated and being disease reservoirs themselves ( Bloomfield and Kumar, 2009 ), hence soap substitutes are not regarded as adequate in this study.…”
Section: Analysesmentioning
confidence: 99%